2021
DOI: 10.3390/ma14164457
|View full text |Cite
|
Sign up to set email alerts
|

Replacement Process of Carbonate Apatite by Alveolar Bone in a Rat Extraction Socket

Abstract: The objective of this study was to investigate a bone graft substitute containing carbonate apatite (CO3Ap) to analyze bone replacement and the state of bone formation in vitro and in vivo compared with autogenous bone (AB) or control. An osteoclast precursor cell line was cultured with AB or CO3Ap, and morphological analysis using scanning electron microscopy and a tartrate-resistant acid phosphatase activity assay were performed. The right maxillary first and second molars of Wistar rats were extracted and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…To surpass the efficacy of previous HC scaffolds and satisfy these requirements, an effective approach is to control the chemical composition and pore structure of the HC scaffold, which can crucially affect its osteoconductivity and resorption. In terms of the chemical composition, carbonate apatite (CAp) is resorbed by the osteoclasts at a similar pace as that of new bone formation and can thus be replaced with new bone (Doi et al, 1998;Zhang et al, 2021). In contrast, hydroxyapatite (HAp) is not resorbed and beta-tricalcium phosphate (β-TCP) is resorbed prior to new bone formation (Ishikawa et al, 2018;Hayashi et al, 2019bHayashi et al, , 2020b.…”
Section: Introductionmentioning
confidence: 99%
“…To surpass the efficacy of previous HC scaffolds and satisfy these requirements, an effective approach is to control the chemical composition and pore structure of the HC scaffold, which can crucially affect its osteoconductivity and resorption. In terms of the chemical composition, carbonate apatite (CAp) is resorbed by the osteoclasts at a similar pace as that of new bone formation and can thus be replaced with new bone (Doi et al, 1998;Zhang et al, 2021). In contrast, hydroxyapatite (HAp) is not resorbed and beta-tricalcium phosphate (β-TCP) is resorbed prior to new bone formation (Ishikawa et al, 2018;Hayashi et al, 2019bHayashi et al, , 2020b.…”
Section: Introductionmentioning
confidence: 99%
“…The OECs and FBs morphology on CO 3 Ap or HAp plates (diameter 10.0 mm, thickness 0.8 mm), which was kindly provided by GC (Tokyo, Japan), was evaluated by scanning electron microscopy (SEM) [ 12 ] (Fig. 2 A).…”
Section: Methodsmentioning
confidence: 99%
“…Rats received care following the guidelines established by Kyushu University (approval number: A29-227-0). Extraction and transplant was performed as previously reported [ 12 ]. Briefly, 6-week-old Wistar rats (72 males; 120–150 g) had extraction of the maxillary right first and second molars under systemic anesthesia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CAP promotes osteoblast differentiation and CAP artificial bones have high bone conductivity [ 12 , 13 ]. A comparison between CAP bone prostheses and autologous bone revealed that CAP was similarly absorbed and replaced by bone in osteoclast precursor cell-culture experiments and in a rat tooth extraction socket model [ 14 ]. In addition, CAP bone prostheses showed promising results in the biopsy–histological assessment upon implant entry and three years after implantation in two-way cases of maxillary sinus floor elevation [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%